Exercise tolerance in breast cancer patients during radiotherapy after aerobic training - Milecki, Piotr; Hojan, Katarzyna; Ozga-Majchrzak, Owidia; Molińska-Glura, Marta (Contemporary Oncology/Współczesna Onkologia, 2013)
Aim of the study : In spite of the introduction of dose constraints based on patient individual assessment techniques for radiation therapy (RT), some side effects from the heart and lungs are observed. Regular physical exercises improve efficiency, which was confirmed in clinical trials. The aim of this study was to evaluate endurance exercise tolerance and the impact of aerobic training (AT) on selected clinical parameters in breast cancer patients during RT. Material and methods: This study involved 46 women with breast cancer who were irradiated using conformal technique (3DCRT) to a total dose of 50 Gray during a 5-week course of RT. In this period 25 patients (group A) simultaneously performed AT, and the rest of the patients, without rehabilitation (group B), undertook irregular physical activity on their own. The exercise tolerance was assessed through the 6-minute walk test (6MWT) using: oxygen saturation (SO2), heart rate (HR), blood pressure (BP), 6-minute walk distance (6MWD) and dyspnea scale. Results: After AT in group A, a statistically significant (p 0.05), and 6MWD was increased (p < 0.05). In group B, after RT, an increase (p < 0.05) in HR was observed after the test as well as dyspnea. Oxygen saturation in both groups was not significantly changed. Conclusions : The results of our study showed that regular AT after just 6 weeks caused an improvement in exercise tolerance parameters with a substantial decline in dyspnea in breast cancer patients receiving RT.